Effect of helium and silver ions co-implanted into polycrystalline silicon carbide at 350 °C on structural evolution and migration behaviour of silver - Hlatshwayo, Thulani Thokozani (University of Pretoria, 2022)
Dissertation (MSc (Physics))--University of Pretoria, 2022.